Performance Appraisers as Test Developers - Banks, Cristina G.; Roberson, Loriann (Academy of Management Review, 1985)
Performance appraisal is reinterpreted as a test development task, and the appraiser is examined in terms of how well he/she can utilize ratee information validly in judging performance. Appraisal formats and appraiser training programs are critically evaluated as aids for developing good tests. New directions in format development and training are suggested for increasing appraisal accuracy.